Peran Sumber Daya Manusia Terampil (alisis kritis Resolusi Problem Pendidikan Pondok Pesantren) - Ridlowi, Achmad (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Religious education conducted by pesantren has a large role in developing multicultural theology. Borrowing the philosophy of education, education for liberation is not for domination. Education must be a process of liberation, not socio-cultural taming. Education aims to work on human reality and therefore, methodologically rests on the principles of action and total reflection, namely the principle of acting to change the oppressive reality.For this reason, the challenges of pesantren are no longer focused on empowering human resources, by making programs, such as craft courses with tools, tools and machines, sewing, carpentry, home furnishings, farming and gardening, welding and electrical engineering . Poesantren is now faced with the challenge of multiculturalism that has become a social reality. Keywords: Pesantren Concept, Pesantren Design, Multicultural Education.